Carbonate slope morphology revealing sediment transfer from bank-to-slope (Little Bahama Bank, Bahamas). (May 2017) - Mulder, T.; Joumes, M.; Hanquiez, V.; Gillet, H.; Reijmer, J.J.G.; Tournadour, E.; Chabaud, L.; Principaud, M.; Schnyder, J.S.D.; Borgomano, J.; Fauquembergue, K.; Ducassou, E.; et al.
Abstract: New high-quality multibeam and high-resolution seismic data reveal new observations on sediment transfer and distribution and margin morphometrics in the uppermost slope of Northeastern Little Bahama Bank between 20 and 300 m water depth. The echofacies/backscatter facies show an alongslope sediment distribution forming successive strips. The upper part of the uppermost slope corresponds to the alternation of several submerged coral terraces and escarpments that could be related to Late Quaternary sea-level variations. The terraces could either be related to periods of stagnating sea-level or slow-down in sea-level change and therefore increased erosion by waves, or periods of accelerated sea-level rise since the Last Glacial Maximum. Terraces could therefore be related to coral construction and drowing. The medium part corresponds to the marginal escarpment, a steep cemented area. The lower part of the uppermost slope shows a discontinuous Holocene sediment wedge with varying thickness between 0 and 35 m. It is separated from the upper part by a zone of well-cemented seafloor associated with the marginal escarpment. Passing cold fronts result in sediment export caused by density cascading. The associated sediment fall-out and convective sedimentation can generate density currents that form this wedge and eventually flow through linear structures on the upper slope. The survey reveals the presence of recently active channels that extend over the entire uppermost slope and interrupt the wedge. The channels connect shallow tidal channels to submarine valleys connected to the proximal part of canyons. They directly feed the canyons with platform-derived sediment forming low-density turbidity currents and could supply the deepest part of the system with coarse-grained sediment directly exported from the carbonate platform. Highlights: High-definition mapping of the uppermost part of a carbonate slope. Evidence for carbonate platform-slope sediment transfer. Identification of Quaternary terraces and escarpments related to sea-level changes.